O ensino de História e as representações sobre os povos indígenas Krahô - Sales, Nívia Alves (Universidade Federal do Tocantins, 2022)
The present research work entitled The Teaching of History and Representations about the Krahô Indigenous Peoples, has as its primary objective to identify the Representations about the indigenous peoples present in the imagination of the students of the 3ª grade of High School at School Impact in Guaraí /TO, as secondary objectives, proposes to describe the representations constituted for the Teaching of History in relation to indigenous peoples, seeking to contextualize the importance of meaningful learning for the teaching of history, thus identifying the representations present in the students' imagination about indigenous peoples and , finally, proposing the development of actions and support materials for the Teaching of History on the representations related to the Krahô indigenous peoples of Tocantins. The study is of a qualitative nature. The approach was based on action research, with the research locus at School Impact Guaraí and the Krahô Indigenous Village. Conversation circles was the enabling strategy for dialogue and consequent listening to students, a 3ª grade high school class, which participated in the research. In addition to this dialogue, the research also included bibliographic sources and iconography of the Krahô peoples available on the socio-environmental website. As a result of the research, I propose an interactive manual for a virtual exhibition on indigenous history and culture, which can be used by both indigenous and non-indigenous teachers, especially in history classes.